Community structure and post-monsoonal distribution of icthyoplankton in Kuantan river, Malaysia - Akbar John, B.; Hassan, S; Nur, Hanisa; Yunus, Kamaruzzaman; Sha, Kadhar (Razi Publishing, 2017)
Present study was aimed to investigate the community structure and size distribution of Icthyoplankton sampled from Kuantan River, Malaysia. Sampling was conducted from May 2015 to August 2015 using modified bubu light trap in Kuantan river and its immediate tributary (Belat river). A total of 78 larvae representing 4 families and 6 genus were sampled and size distribution were measured using Dino capture 2.0v portable microscope. Significant influences of selected water quality parameters on the distribution of Icthyoplankton were observed (p < 0.05). Representatives of larvae belong to gobiidae, eleotridae ambassidae and leiognathidae were recorded during sampling and few larvae were unable to be distinguished morphologically and hence stored for further DNA barcoding. Modified bubu light trap method designed and adopted in this study can be successfully used to sample Icthyoplankton in rivers where the depth and turbidity are the key limiting factors during sampling